Thanatosean Episteme in Philip Ridley’s Mercury Fur - Rosheed, Mostafa; Ubeid, Ahmed (Al-Adab Journal, 2023)
The shift in the critical perspective splits an episteme in two. A line of demarcation identical to the paradigm shift separates the new epistemes in a way that the critical insight should differ drastically on both sides of the line. Michel Foucault sorts these historical epistemes as Renaissance and Classical epistemes, then he included the Modern episteme as a latter historical era, and the line of distinction between one episteme and another is the critical insight that the involved mentality adopts. When it comes to the source of the influence of human behavior, the change in perspective in the consideration of the source of the influence is clarified in the comparison between the pre-Freudian versus the post-Freudian understandings of human beings. It means that with the consideration of two major depressions, the pre-Freudian thought believed that the driving forces of human beings are external. Whereas the post-Freudian understanding reconsidered the influence on human behavior as ramifications of the sub-consciousness that eventually affect the consciousness of human beings. This paper intends to examine Philip Ridley’s Mercury Fur (2005) in terms of the Russian Formalist’s defamiliarization aspects. The deployment of such techniques implicates the advancement of the dystopian irregularities on the stage over the regularly implied didactic methodologies. The use of the Foucauldian epistemes distinguishes the deployed defamiliarizing aspects as identified with a difference from the de Sassurean sign analogy. The paper concludes with the defamiliarized elements as the focal points of the plays that adopt Thanatos as their methodology.